Competitive disruption of the tumor-promoting function of membrane type 1 matrix metalloproteinase/matrix metalloproteinase-14 in vivo. - Nonaka, T; Nishibashi, K; Itoh, Y; Yana, I; Seiki, M (2005)
Membrane type 1 matrix metalloproteinase (MT1-MMP) is a potent modulator of the pericellular environment and promotes tumor cell invasion and proliferation in many types of tumor. The activation of proMMP-2 and processing of collagen I by MT1-MMP have been thought to be important for its tumor-promoting function. These activities can be inhibited by mutant forms of MT1-MMP lacking the catalytic domain. However, the effect of such dominant-negative mutants has never been evaluated in vivo. Various mutants lacking the catalytic domain (dCAT) were prepared and confirmed to inhibit MT1-MMP activity in human fibrosarcoma HT1080 cells, and tumor cells expressing these mutants were implanted s.c. into nude mice to monitor tumor formation. Only the membrane-anchored form of a dCAT construct through the transmembrane domain [dCAT(1)] showed potent antitumor activity not only in HT1080 cells but also in gastric carcinoma MKN28 and MKN45 cells expressing MT1-MMP. A soluble form of dCAT lacking the transmembrane domain did not show such activity. The expression of dCAT(1) in MKN28 or MKN45 further prevented the metastatic spread of tumor cells into the peritoneal cavity; however, dCAT(1) showed no effect against TMK-1, another gastric carcinoma cell line expressing no MT1-MMP. It is of note that the tumorigenicity of TMK-1 cells enhanced by MT1-MMP overexpression was, in turn, canceled by the additional expression of dCAT(1). Thus, MT1-MMP expressed in tumor cells seems to play a pivotal role in tumor growth in mice. The results also suggest new possibilities to abrogate the tumor-promoting function of MT1-MMP other than the conventional protease inhibitor-based approach.